Flow of submersible elements by vibratory boiling layers - Русанов, Сергей Аркадьевич; Никитенко, Ганна Витальевна; Луняка, Клара Васильевна (Eastern-European Journal of Enterprise Technologies, 2012)
The article represents the behavior of dispersed materials during the flowing of submersible elements. Some research results, concerning this type of devices, are given. The central purpose of the research is to gain enough experimental background concerning the hydrodynamics of submersible elements (coil sections) flowed by vibratory boiling layer to make a single computing method and to design similar devices. The results obtained show that the flowing of submersible elements reveals additional peculiarities of the flow of vibratory boiling layer from the vibratory rheological approach. This means, while flowing cylindrical submersible elements the transversal circulating current appears. This indicates the appearance of transverse viscosity of pseudo homogeneous continuum. The diagrams of plot of vibratory carry speeds against the angle of the platform inclination and the vibration frequency were given. The streamlines for the flow of submersible elements by vibratory boiling layer were obtained. The streamlines pattern becomes apparent when the number of cylinders is more than two.